Anatomical and histopathological evaluation of the bursa, thymus and spleen of broiler chickens raised in new or reused litter - Tambini A., Antonio (2010)
The anatomo-histopathological development of the bursa, thymus and spleen of broiler chickens raised in new and reused litter through five campaigns was evaluated. Two hundred and fifty male chickens of the Ross 308 line were raised, half in new and half in reused litter. On a weekly basis, the morphometric indexes of bursa, thymus and spleen, and the relation bursa/spleen were recorded. The lymphoid organs were evaluated by histopathology and ELISA test was used to determine antibody titres for Gumboro, Newcastle, Infectious Bronchitis, Infectious Anemia, and Reovirus at the beginning and end of the study (49 days). Statistical difference was found (p<0.05) for weight and morphometric index of the bursa (6.57 ± 2.07 g and 1.67 ± 0.49 for birds raised on new litter and 2.74 ± 1.35 g and 0.70 ± 0.36 for birds in reused litter), but not on body weight between groups. Better results were observed on body weight and morphometric index of the spleen and for the relation bursa/spleen (p<0.05). Similar differences were found for the thymus but without statistical difference. The histopathological evaluation showed severe bursal atrophy in birds reared on new (1/5) and reused (4/5) litters, while the serology revealed 3 out of 15 birds with elevated antibody titres against Gumboro in the group of reused litter. These observations indicated that the group of reused litter was challenged with a low pathogenicity strain of Gumboro or with vaccine strains that have persisted in the litter. It was concluded that reused litter from healthy chicken can be safety reused.